The Effect of Phosphatation and Granulation Zeolite in the Adsorption of Cr(VI) - Sri Wardhani; Reno Sunarinda Endrayana; Danar Purwonugroho (Chemistry Department, The University of Brawijaya, 2017)
The purpose of this research to study effect of contact time on adsorption of Cr(VI) ion using Granules Alumino Silico Phosphate (GASP) and the effect of Cr (VI) concentration on adsorption capacity at GASP. The GASF synthesis process is carried out in several main stages: 1) activation of zeolite with addition of HCl, 2) zeolite phosphatation with addition of NH4H2PO4 ratio Si/P = 1/6 at 235ᴼC for 5 hours, 3) how make GASP with addition of zeolite phosphate (Alumino Silicone Phosphate) and chitosan gel with a syringe pump speed of 50 mL/min. GASP is characterized using XRF, FT-IR and SAA. The contact time effect is tested using 0.1 g of GASF in K2CrO4 100 mg/L with a contact time variation of 0.5; 1.0; 1.5; 2.0 and 2.5 hours. The concentration effect on adsorption capacity is tested out using 0.1 g of GASP in K2CrO4 with concentration variation 25, 50, 75, 100 and 150 mg / L for 2 hours (optimum contact time). The adsorption capacity can be determined using the Langmuir equation. XRF characterization results showed a decrease in SiO2 levels of 18.10% and Al2O3 by 2.2% after phosphatation process. FTIR characterization results indicate the presence of O-H, N-H and C-H chitosan on absorption bands 1-3. The success of the phosphatation process was evidenced by the shift of wave numbers to the lower regions in the bands 7, 9 and 12 the absorption of tetrahedral silica and alumina shifted to bands 8, 10 and 13 tetrahedral phosphate uptake in accordance with Hooke's law. The result of the research showed that the optimum contact time occurred in the adsorption process for 2 hours. The concentration variation was directly proportional to the increase of the adsorbed Cr (VI) ion mass. The presence of phosphatation and chitosan addition process can increase the value of adsorption capacity by 48,077 mg / g.